Pengaruh Pemberian Metode Mewarnai Gambar Terhadap Perkembangan Anak Usia Prasekolah Di TK Unggulan Terpadu Al-Kautsar Jabon Dan TK Dharmawanita Gayaman Mojokerto - Ika Suhartanti; Henry Sudiyanto; Nurul Mawaddah (Sekolah Tinggi Ilmu Kesehatan Majapahit Mojokerto, 2020)
The preschool period was a very important period in the development of children so that stimulation needs to be done, one of which was by providing drawing coloring skills where this activity can increase the chance of children to express, train motor nerves, creativity and train children's imagination. This study aims to analyzed the effect of giving drawing coloring methods to the development of pre-school age children. The type of research used was quasi-experimental Quasy research using the Pretest-posttest Control Group Design method. The sample used 40 respondents, 20 groups intervened in Al-Kautsar Jabon Mojokerto TKUT and 20 control groups at the Dharma Wanita Gayaman Mojokerto Kindergarten. The sampling technique used in this study was purposive sampling. The measuring instrument used was KPSP (Pre Development Screening Questionnaire). Test data using Paired Sample Test and Independent Sample Test statistics. Paired Sample Test results in the intervention group p = 0,000 means that there were differences in development before and after coloring the image, whereas in the control group the value of p = 0.134 means that there is no difference in development in preschool children. The results of the Independent Sample Test showed that p = 0,000 means that there is an effect of giving the coloring method to the development of pre-school age children. It was expected that preschoolers will get more stimulation in coloring pictures both at home by parents and at school by their teachers to gain direct experience of active, creative and fun learning